Influence of Nanolime and Curing Period on Unconfined Compressive Strength of Soil - Panbarasi Govindasamy; Mohd Raihan Taha; Jamal Alsharef; Kowstubaa Ramalingam (Applied and Environmental Soil Science)
This paper presents the improvement of the unconfined compressive strength (UCS) of soil by mixing different percentages of nanolime and 5% lime with soil. The UCS of treated soil increased significantly over curing time with increasing percentage of nanolime. The optimum results were reached at only 0.5% nanolime admixtures which were much higher than 5% lime admixture. This may be due to higher ability of nanolime to flocculate and agglomerate the soil particles compared with the lime. In addition, the lime could fill only the micropores while nanolime could fill the micro- and nanopores as well. The strength gain is inversely proportional to the remolded moisture content and curing period. However, when the content of nanolime used is larger than 0.5%, nanolime particles are not uniformly dispersed. Therefore, a weak area in the form of voids is created, consequently the homogeneous hydrated microstructure cannot be formed, and finally the strength will decrease.